Proton- and ammonium-sensing by histaminergic neurons controlling wakefulness - Yanovsky, Yvgenij; Zigman, Jeffrey M.; Kernder, Anna L.; Bein, Alisa; Sakata, Ichiro; Osborne-lawrence, Sherri; Haas, Helmut L.; Sergeeva, Olga A. (Frontiers in Systems Neuroscience, 2012)
Orexinergic and histaminergic neurons in the posterior hypothalamus are involved in the control of arousal. Extracellular levels of acid /CO2 are fundamental physicochemical signals controlling wakefulness and breathing. Acidification excites orexinergic neurons like the chemosensory neurons in the brain stem. Hypercapnia induces c-Fos expression, a marker for increased neuronal activity, in the rat histaminergic tuberomamillary nucleus (TMN), but the mechanisms of this excitation are unknown. Acid-sensing ion channels (ASICs) are gated by protons and also by ammonium. Recordings in rat brain slices revealed now that acidification within the physiological range (pH from 7.3 to 7.0) as well as ammonium chloride (5mM) excite histaminergic neurons. We detected variable combinations of 4 known types of ASICs in single TMN neurons, along with the pharmacological properties of pH-induced current. At pH 7.0 however, activation of ASICs in TMN neurons was negligible. Block of type I metabotropic glutamate receptors abolished proton- but not ammonium- induced excitation. Mouse TMN neurons were identified within a novel HDC-Cre transgenic reporter mouse line. In contrast to the rat these lacked pH 7.0-induced excitation and showed only a minimal response to the mGluR I agonist DHPG (0.5µM). Ammonium-induced excitation was similar in mouse and rat. Thus glutamate, which is released by glial cells and orexinergic axons amplifies CO2/acid-induced arousal through the recruitment of the histaminergic system in rat but not in mouse. These results are relevant for the understanding of neuronal mechanisms controlling H+/CO2-induced arousal in hepatic encephalopathy and obstructive sleep apnoea. The new HDC-Cre mouse model will be a useful tool for studying the physiological and pathophysiological roles of the histaminergic system.